Bridging The Gap: Aligning Transportation Education With Industry Demands In Indonesia - Retno Sawitri Wulandari; Larsen Barasa; Jaya Alamsyah; April Gunawan Malau; Marudut Bernadtua Simanjuntak (International Journal of Educational Development, 2024)
This research examines the alignment between transportation education at the Maritime Institute of Jakarta and industry demands in Indonesia, focusing on multimodal transportation. Through qualitative analysis of 50 cadets, the study reveals a strong emphasis on curriculum relevance and practical skills development. However, there are opportunities for improvement in areas such as technological integration, professional development, and industry exposure. Recommendations include enhancing technological integration, increasing industry exposure, strengthening professional development, improving curriculum relevance, fostering industry collaboration, enhancing practical skills development, and emphasising ethical and legal aspects. These recommendations aim to better prepare students for the dynamic and technology-driven nature of the transportation industry. Overall, this research highlights the importance of continuous improvement in transportation education to meet the evolving demands of the industry and contribute to the development of a skilled and competitive workforce in Indonesia.